1995
DOI: 10.1063/1.531238
|View full text |Cite
|
Sign up to set email alerts
|

Topological BF theories in 3 and 4 dimensions

Abstract: May 3, 1995 hep-th/9505027, IFUM 503/FT prepared for the special issue of Journal of Math. Phys. on Quantum geometry and diffeomorphism-invariant quantum field theory P.A.C.S. 02.40, 11.15, 04.60 AbstractIn this paper we discuss topological BF theories in 3 and 4 dimensions. Observables are associated to ordinary knots and links (in 3 dimensions) and to 2-knots (in 4 dimensions). The vacuum expectation values of such observables give a wide range of invariants. Here we consider mainly the 3 dimensional case, w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
141
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 99 publications
(141 citation statements)
references
References 25 publications
0
141
0
Order By: Relevance
“…As a gauge theory, CS theory with inhomogeneous gauge group is equivalent to pure BF theory and should therefore "see" knots at least for ISU(2) gauge group, as was shown by Cattaneo et al [9,10,11]. Therefore, we need a procedure that will extract some non trivial information regarding the knot in our setting.…”
Section: Proofmentioning
confidence: 99%
See 1 more Smart Citation
“…As a gauge theory, CS theory with inhomogeneous gauge group is equivalent to pure BF theory and should therefore "see" knots at least for ISU(2) gauge group, as was shown by Cattaneo et al [9,10,11]. Therefore, we need a procedure that will extract some non trivial information regarding the knot in our setting.…”
Section: Proofmentioning
confidence: 99%
“…In the mid-90's, Cattaneo et al [9,10,11,12] showed that while BF theory with cosmological constant produces the same invariants of knots as the Chern-Simons (CS) theory, the BF theory with no cosmological constant (pure BF theory) and SU(2) gauge group produces invariants that lie in the algebra generated by the coefficients of the Alexander-Conway polynomial. The BF TQFT is completely equivalent to CS theory, however while the equivalence with non-zero cosmological constant maintains the semi-simplicity property of the gauge group, the equivalence when the cosmological constant is set to zero shifts us to a CS theory with a non-semi-simple gauge group.…”
Section: Introductionmentioning
confidence: 99%
“…The generalized Wilson loop in the BV superformalism. We want to define an object that generalizes the observable introduced in [11] for the 3-dimensional BF theory with cosmological term. We shall realize this proposal by introducing the new superform…”
Section: Generalized Wilson Loops In Odd Dimensionsmentioning
confidence: 99%
“…Now we briefly comment on the observables defined in this paper and in [16]. First, they are defined on loops (observables related to higher-dimensional submanifolds are of course of great interest and will be discussed in a forthcoming paper; we refer to [20,11,15] for previous attempts in this direction). Second, the quantum BV formalism requires considering the so-called BV Laplacian (see subsection 4.4) and this forces one to restrict to imbeddings (more precisely, to framed imbeddings).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation